2014
DOI: 10.1159/000365592
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Alternative Drugs to the Tumor Suppressor miR-375 in Esophageal Squamous Cell Carcinoma Using the Connectivity Map

Abstract: Objective: The aim of this study was to identify alternative compounds to the tumor suppressor miR-375 using the connectivity map (CMAP) and to validate the antitumor effects of the identified drugs in esophageal squamous cell carcinoma (ESCC). Methods: Gene profiling of miR-375-treated TE2 and T.Tn cells was applied in order to search the CMAP database. Among the compounds identified using the CMAP, we focused on 8 drugs [(-)-epigallocatechin-3-gallate, metformin, rosiglitazone among others], excluding 2 drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…We searched drugs which induce similar gene expression style by connectivity map and found metformin. It restrained the increase of ESCC cell lines, TE2 and T.Tn …”
Section: Introductionmentioning
confidence: 99%
“…We searched drugs which induce similar gene expression style by connectivity map and found metformin. It restrained the increase of ESCC cell lines, TE2 and T.Tn …”
Section: Introductionmentioning
confidence: 99%
“…Unsupervised clustering analysis illustrated a distinct miRNA expression profile in metformin-treated KYSE30 cells [ 50 ]. Additional studies examined the gene expression profiles of numerous miRNAs in ESCC cell lines [ 67 , 68 , 69 ]. These analyses employed microarray data in conjunction with the Connectivity Map (CMAP) database, revealing crucial biological functions associated with these miRNAs.…”
Section: Understanding Metformin’s Molecular Mechanisms In Ecmentioning
confidence: 99%
“…These analyses employed microarray data in conjunction with the Connectivity Map (CMAP) database, revealing crucial biological functions associated with these miRNAs. These functions encompassed processes such as development, differentiation, apoptosis, and proliferation, elucidating the intricate connections between metformin, genes, and the pathogenesis of ESCC [ 67 , 68 , 69 ] In particular, metformin might activate the TMCO3 and PLA2G4A genes, which are tumor suppressor genes upregulated by miR-375 and have a tumor-suppressive function in themselves as an alternative substance to miR-375 [ 67 ]. Investigating the communication between hypoxic and normoxic cells via exosomes, this study identified exo-miR-340-5p as a key player in the transfer of radioresistance.…”
Section: Understanding Metformin’s Molecular Mechanisms In Ecmentioning
confidence: 99%
“…Metformin inhibits the proliferation of ESCC cells [11]. We previously reported that microRNA-375 exerted an antitumor effect on ESCC cells and that metformin altered gene expression and inhibited ESCC cell proliferation similar to microRNA-375 [12]. We also reported that nuclear factor-kappa B was important for mediating the antitumor effects of metformin, such as inhibition of tumor growth and epithelial-mesenchymal transition [13].…”
Section: Introductionmentioning
confidence: 99%